Vaccine-based immunotherapy for glioblastoma. (July 2013) - Thomas, Alissa A; Fisher, Jan L; Ernstoff, Marc S; Fadul, Camilo E
SUMMARY Glioblastoma remains the most lethal human brain tumor, despite the advent of multimodal treatment approaches. Because immune tolerance plays an important role in tumor progression, adding immunotherapy has become an attractive and innovative treatment approach for these aggressive tumors. Several early-phase clinical trials have demonstrated that vaccine-based immunotherapies, including dendritic cell therapy, peptide-based vaccines and vaccines containing autologous tumor lysates, are feasible and well tolerated. These trials have revealed promising trends in overall survival and progression-free survival for patients with glioblastoma, and have paved the way for ongoing randomized controlled trials.